Detecting Sepsis: Are Two Opinions Better Than One?. Issue 4 (1st April 2017) - Bhattacharjee, Poushali; Churpek, Matthew M.; Snyder, Ashley; Howell, Michael D.; Edelson, Dana P.
Abstract : The diagnosis of sepsis requires that objective criteria be met with a corresponding subjective suspicion of infection. We conducted a study to characterize the agreement between different providers' suspicion of infection and the correlation with patient outcomes using prospective data from a general medicine ward. Registered nurse (RN) suspicion of infection was collected every 12 hours and compared with medical doctor or advanced practice professional (MD/APP) suspicion, defined as an existing order for antibiotics or a new order for blood or urine cultures within the 12 hours before nursing screen time. During the study period, 1386 patients yielded 11, 489 screens, 3744 (32.6%) of which met at least 2 systemic inflammatory response syndrome (SIRS) criteria. Infection was suspected by RN and MD/APP in 5.8% of cases, by RN only in 22.2%, by MD/APP only in 7.2%, and by neither provider in 64.7%. Overall agreement rate was 80.7% for suspicion of infection (κ = 0.11, P < 0.001). Progression to severe sepsis or shock was highest when both providers suspected infection in a SIRS‐positive patient (17.7%), was substantially reduced with single‐provider suspicion (6.0%), and was lowest when neither provider suspected infection (1.5%) ( P < 0.001). Provider disagreement regarding suspected infection is common, with RNs suspecting infection more often, suggesting that a collaborative model for sepsis detection may improve timing and accuracy.